Selection by noncontrast computed tomography with or without computed tomography angiography versus computed tomography perfusion for endovascular therapy in patients with acute ischemic stroke: a systematic review and meta‐analysis - Zhang, Yang; Zhao, Yang; Deng, Bowen; Wu, Simiao; Nogueira, Raul G.; Abdalkader, Mohamad; Nagel, Simon; Michel, Patrik; Qiu, Zhongming; Yang, Qingwu; Miao, Zhongrong; Huo, Xiaochuan; et al. (Journal of the American Heart Association, 2025)
Background - The effect of imaging selection on endovascular therapy for acute ischemic stroke remains debated. We compared the efficacy and safety of imaging modalities using computed tomography perfusion with using noncontrast computed tomography (NCCT)±computed tomography angiography. - Methods - Studies from PubMed, Embase, and Cochrane Library up to March 1, 2024, were analyzed. Sixteen studies (12 199 patients) assessed functional independence (modified Rankin Scale score of 0-2 at 90 days) using odds ratios (ORs). This study was registered with the International Prospective Register of Systematic Reviews (CRD42024519554). - Results - No significant differences were observed in functional independence (OR, 1.09 [95% CI, 0.98-1.21]), modified Rankin Scale score of 0 to 1 (OR, 1.07 [95% CI, 0.88-1.29]), 0 to 3 (OR, 1.04 [95% CI, 0.92-1.18]), thrombolysis in cerebral infarction 2b to 3 (OR, 1.08 [95% CI, 0.95-1.22]), symptomatic intracranial hemorrhage (OR, 0.87 [95% CI, 0.74-1.04]), and any intracranial hemorrhage (OR, 0.95 [95% CI, 0.80-1.12]) between the computed tomography perfusion and NCCT group. There was a significantly lower odds of death during follow‐up in the computed tomography perfusion group compared with the NCCT group (OR, 0.78 [95% CI, 0.70-0.88]). Comparison of modified Rankin Scale score of 0 to 2 significantly favored NCCT selection for patients with large cores (Pinteraction=0.05). Risk of bias assessment using the Cochrane risk assessment tool revealed concerns in 1 randomized control trial, while observational and post hoc studies assessed with Risk of Bias in Nonrandomized Studies of Interventions I showed moderate (2 studies), serious (11 studies), and critical (2 studies) risk of bias. - Conclusions - These findings indicate that patients undergoing endovascular therapy selected with computed tomography perfusion had a similar functional prognosis compared with those selected with NCCT but had lower odds of death during follow‐up. NCCT‐defined large‐core patients had better functional outcomes.